Socialization of Stone Craft in Muntilan on The Community Empowerment Process - Istanto, Riza; Rohendi Rohidi, Tjetjep; Triyanto, Triyanto (Catharsis, 2019)
The purpose of this study was to analyze the process of socializing the stone craft in Muntilan in empowering the cultural potential of the community. This research was conducted at the center of the Muntilan stone craft, namely Tamanagung Village, Muntilan District, Magelang Regency, Central Java Province. The sociology approach and case study design were used in this research. Data was collected by observation, interview, and documentation techniques. To obtain validity of the data collected triangulation of data is done through steps a) comparing the results of interviews, observations, and documents obtained; b) comparing an informant's personal confession with his statements in public or when a group discussion takes place; c) comparing opinions at the time of research with situations that have occurred throughout history; d) comparing opinions between ordinary people, educated, and bureaucrats. Data analysis includes the stage of selecting a problem, summarizing the problem, collecting data, analyzing the data, and writing the results (including drawing conclusions at the end of the analysis). The results of the study showed that empowerment was carried out in the Batu Kriya community agents through the socialization process. The stone craft socialization process includes the preparation stage, namely the introduction of knowledge about materials, equipment, and techniques; the stage of imitating through the practice of making stone crafts under the direction of experts (expert craftsmen); the stage of acting through working together with skilled craftsmen (nyantrik); and the stage of acceptance of collective norms that occur when the crafters make stone carving activities as a profession. The suggestion that the authors propose through this research is that coaching in advancing traditional arts must be based on joint commitment through crafters and the public as well as participants or communities so as to create independence and prosperity for them.